Influence of Dates of Sowing and Nitrogen Levels on Growth and Yield of Kharif Maize under Irrigated Conditions in South Telanagana Agro-climatic Zone of Andhra Pradesh, India - Rani, P. Leela; Sreenivas, G.; Reddy, D. Raji; Rao, V. Praveen; Surekha, K.; Sankar, A. Siva (International Journal of Bio-resource and Stress Management, 2023)
An Experiment was carried out during kharif 2009 and 2010 at Agricultural Research Institute, Rajendranagar, Hyderabad, India. with four dates of sowing (7th July, 21st July, 6th and 22nd Aug in 2009 and 18th June, 02nd July, 17th July and 02nd Aug in 2010) as main plot and five nitrogen levels (N0: 0 kg ha -1(control), N1:100 kg ha -1, N2: 200 kg ha -1, N3:300 kg ha -1and N4: 400 kg ha -1) as sub-plot in split plot design replicated thrice. In 2009, 21-July sown crop recorded significantly higher plant height (185 cm), LAI (2.489), dry matter (103.7 g plant-1), grain (6809 kg ha-1) and stover yield (6590 kg ha-1), harvest index (47.9), net returns (` 30429 ha-1) and benefit cost ratio (2.08), and was on par with 7th July sown crop. On the other hand, in 2010, plant height (175 cm), LAI (2.464), dry matter (89.9 g plant-1), grain yield (6605 kg ha-1), stover yield (6537), harvest index (47.2), net returns (` 28770 ha-1) and benefit cost ratio (2.01) of 18th June sown crop was on par with 2nd July sown crop. Significantly higher growth, yield, (7778 kg ha-1, 7646 kg ha-1), HI (51.3, 51.7), net returns (` 38502 and 37469) and benefit cost ratio (2.37 and 2.39) was observed with 200 kg N ha-1 respectively during both the years of study. Sowing beyond 21st July in 2009 and 17th July in 2010 reduced the grain yield by 23% and 14% respectively.